Adolescent sexual and reproductive health research in sub-Saharan Africa: a scoping review of substantive focus, research volume, geographic distribution and Africa-led inquiry - Anthony Idowu Ajayi; Boniface Ayanbekongshie Ushie; Meggie Mwoka; Emmanuel Oloche Otukpa; Caroline W. Kabiru (BMJ Global Health)
Background Previous review studies have not systematically mapped the existing body of knowledge on adolescent sexual and reproductive health (ASRH) in sub-Saharan Africa (SSA). Our scoping review addresses this gap by examining how the body of research on ASRH in SSA has evolved over the past decade, and its present profile, in terms of trends in volume, geographic and substantive focus, and Africa-led inquiry.Methods We used a three-step search strategy to identify English and French peer-reviewed publications and relevant grey literature on ASRH in SSA published between January 2010 and December 2019. Two reviewers screened the titles, abstracts and full texts of publications for eligibility and inclusion.Results A total of 1302 articles were published over the period, rising from 91 in 2010 to 183 in 2015. However, the bulk of the studies (63.9%) focused on six (South Africa, Kenya, Nigeria, Tanzania, Uganda and Ethiopia) of the 46 SSA countries. Ten countries had no ASRH papers, while five others each had only one publication. While issues like HIV (17.2%), sexual behaviours (17.4%) and access to sexual and reproductive health services (13.0%) received substantial attention, only a few studies focused on early adolescence (10–14 years), programme interventions, scaling up of interventions and policy evaluation. Just over half of publications had authors with African institutional affiliations as first authors (51.1%) or last author (53.0%). Sixteen per cent of papers did not include any authors from institutions in Africa.Conclusions Our review demonstrated that research on ASRH is limited in focus and is unevenly distributed across SSA countries. The identified gaps can guide future research and funding to advance ASRH policies and programmes. It is also vital for stakeholders in the research enterprise, including researchers, donors, ethical review boards, and journal editors and reviewers, to implement measures that foster national investigators’ inclusion.